Correlation of 25 Hydroxyvitamin D3 Levels with Blood Pressure and Lipid Profile, in Healthy Individuals - Sari, Mutiara Indah; Sanny, Sanny (Universitas Muhammadiyah Sumatera Utara, 2021)
Vitamin D is a prohormone and its level correlated with several cardiovascular diseases (CVD) biomarker such as blood pressure (systolic and diastolic) and lipid profile (total cholesterol (TC), triglyceride (TG), high density lipoprotein cholesterol (HDL-C) and low density lipoprotein cholesterol (LDL-C). This study aim to analyze correlation of serum 25-hydroxyvitamin D/ 25(OH)D levels with blood pressure and lipid profile in healthy subjects. This cross-sectional study was conducted on 39 healthy subjects from gym in Medan city. Measurement of vitamin D levels using Enzyme Linked Immunosorbent Assay (ELISA). Blood pressure was measured twice after 10 minutes rest using mercury sphygmomanometer. Lipid profile were measured by Cobas 6000 (C510+E610). Correlation of 25(OH)D with blood pressure and lipid profile were analyzed using Spearman correlation test. There was a significant correlation between of 25(OH)D levels and diastolic blood pressure (p = 0.047, r = -0.272), but not in systolic blood pressure and the lipid profile: TC, TG, HDL, and LDL, respectively. (p = 0.159, p = 0.290, p = 0.425, p = 0.492, p = 0.156). This study concluded that 25(OH)D levels was correlated with diastolic blood pressure with low correlation, in that decreasing of 25-hydroxyvitamin D levels will increased diastolic blood pressure.